Speaking of Diversity Language and Ethnicity in Twentieth-Century America - Gleason, Philip (Johns Hopkins University Press, 2019)
Originally published in 1992. In this collection of essays, Philip Gleason explores the different linguistic tools that American scholars have used to write about ethnicity in the United States and analyzes how various vocabularies have played out in the political sphere. In doing this, he reveals tensions between terms used by academic groups and those preferred by the people whom the academics discuss. Gleason unpacks words and phrases-such as melting pot and plurality-used to visualize the multitude of ethnicities in the United States. And he examines debates over concepts such as "assimilation," "national character," "oppressed group," and "people of color." Gleason advocates for greater clarity of these concepts when discussed in America's national political arena. Gleason's essays are grouped into three parts. Part 1 focuses on linguistic analyses of specific terms. Part 2 examines the effect of World War II on national identity and American thought about diversity and intergroup relations. Part 3 discusses discourse on the diversity of religions. This collection of eleven essays sharpens our historical understanding of the evolution of language used to define diversity in twentieth-century America.